Representasi Gaya Hidup Wanita dalam Iklan Fibe Mini di Jepang dan Indonesia: Kajian Analisis Wacana Kritis - Salma Mahira Dewi (IZUMI, 2025)
This study aims to find out about differences in the representation of women in Fibe Mini commercial ads in Japan and Indonesia. The research method used is a descriptive method with critical discourse analysis by Van Dijk (1981). The object of research are Japan and Indonesia Fibe Mini commercial ads uploaded on Youtube Fibe Mini official channel by each country. The result of analysis showed significant differences in the way Fibe Mini advertisements are packaged in Japan and Indonesia regarding digestive health. Japanese ads emphasize the importance of staying healthy for women office workers. Meanwhile, Indonesian ads emphasize maintaining health to get results in one’s appearances, results of a healthy body can affect one’s body that is charming and a face that is radiantly beautiful. Based on findings, it is concluded that there are striking differences is in the portrayal of women’s lifestyles in Japanese and Indonesian ads. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor